GROWING THE SPIRIT OF ENTREPRENEURSHIP THROUGH PRACTICE OF EMPEK-EMPEK PRODUCTION ON HOUSEWIVES IN SEI MENCIRIM VILLAGE, JATI DUSUN II STREET, DELI SERDANG SUBDISTRICT - Hidayati, Hosianna Ayu (Talenta Publisher Universitas Sumatera Utara, 2019)
In order to reduce poverty and create a prosperous society, we are not only challenged to prepare Human Resources who are ready to work, but also must be able to prepare and create the employment by entrepreneurship. Entrepreneurship or have an own business is a dream for many people since there are many benefits can be obtained. In this context, the concern of growing the spirit of entrepreneurship on housewives in the village of Sei Mencirim is based on several reasons. First, by entrepreneurship, housewives are able to help the heads of household in improving family living standards. Second, since housewives have more free time, it is going to be more efficient if used for entrepreneurship. Third, housewives tend to be more skilled at managing time and easily to socialize with others. Thus, to foster this entrepreneurial spirit, it is necessary to familiarize housewives about the importance of entrepreneurship, so that, later, housewives in Sei Mencirim village can understand the importance of entrepreneurship. The objectives of this community service are: (1) To provide a deeper insight of the entrepreneurship importance, especially for housewives in Sei Mencirim Village, Jati Dusun II Street, (2) To see how much housewives’ interest in Sei Mencirim Village, Jati Dusun II Street for entrepreneurship, (3) To share the knowledge about how to see business opportunities for housewives in Sei Mencirim Village, Jati Dusun II Street. The result of this community service activity is the community has been able to make a small group in making the projects for housewives as an alternative that can be used to build the business later and housewives can help improve the family economy without forgetting its role.